Making Brexit work for the environment and livelihoods: Delivering a stakeholder informed vision for agriculture and fisheries. Issue 4 (23rd September 2019) - Stewart, Bryce D.; Burns, Charlotte; Hejnowicz, Adam P.; Gravey, Viviane; O'Leary, Bethan C.; Hicks, Kevin; Farstad, Fay M.; Hartley, Sue E.
Abstract: The decision of the UK to leave the EU has far‐reaching, and often shared, implications for agriculture and fisheries. To ensure the future sustainability of the UK's agricultural and fisheries systems, we argue that it is essential to grasp the opportunity that Brexit is providing to develop integrated policies that improve the management and protection of the natural environments, upon which these industries rely. This article advances a stakeholder informed vision of the future design of UK agriculture and fisheries policies. We assess how currently emerging UK policy will need to be adapted in order to implement this vision. Our starting point is that Brexit provides the opportunity to redesign current unsustainable practices and can, in principle, deliver a sustainable future for agriculture and fisheries. Underpinning policies with an ecosystem approach, explicit inclusion of public goods provision and social welfare equity were found to be key provisions for environmental, agricultural and fishery sustainability. Recognition of the needs of, and innovative practices in, the devolved UK nations is also required as the new policy and regulatory landscape is established. Achieving the proposed vision will necessitate drawing on best practice and creating more coherent and integrated food, environment and rural and coastal economic policies. Our findings demonstrate that "bottom‐up" and co‐production approaches will be key to the development of more environmentally sustainable agriculture and fisheries policies to underpin prosperous livelihoods. However, delivering this vision will involve overcoming significant challenges. The current uncertainty over the nature and timing of the UK's Brexit agreement hinders forward planning and investment while diverting attention away from further in‐depth consideration of environmental sustainability. In the face of this uncertainty, much of the UK's new policy on the environment, agriculture and fisheries is therefore ambitious in vision but light on detail. Full commitment to co‐production of policy with devolved nations and stakeholders also appears to be lacking, but will be essential for effective policy development and implementation. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.